The great acceleration : an environmental history of the anthropocene since 1945 - McNeill, John Robert; Engelke, Peter (Peter O.) (The Belknap Press of Harvard University Press, 2014)
The pace of energy use, greenhouse gas emissions, and population growth has thrust the planet into a new age--the Anthropocene. Humans have altered the planet's biogeochemical systems without consciously managing them. The Great Acceleration explains the causes, consequences, and uncertainties of this massive uncontrolled experiment.